The determinants of voluntary traceability standards: The case of the wine sector - Stefanella Stranieri; Alessia Cavaliere; Alessandro Banterle (Wine Economics and Policy, 2018)
The aim of this paper is to study the determinants leading firms to choose among different kinds of voluntary traceability standards in the wine sector. To achieve this goal, we referred both to individual and institutional-level determinants, which are identified to play an important role in the literature related to the implementation of quality and safety standards. In specific, we referred to two theoretical approaches to better understand the industry behaviour towards the adoption of voluntary traceability, i.e. the Theory of Reasoned Action and the Institutional Theory. We developed a vis-à-vis survey through a questionnaire on a sample of Italian wineries approached during the most important Italian wine exhibitions in 2016. The results suggest that when wineries show positive cognitive beliefs towards voluntary traceability standards, they will probably implement complex traceability systems, which require high investments and efforts for their management. On the contrary, when the institutional environment plays a key role in the perception of wine processors, a simple and flexible traceability system seems to be preferred.
Keywords: 330; Cognitive determinants; Institutional determinants; Voluntary traceability standards